Regimes of memory - Radstone, Susannah; Hodgkin, Katharine, 1961- (Routledge studies in memory and narrative, 2003)
This volume represents, explores and interrogates the current developments in the study of memory, engaging directly with the place of memory in culture, and with memory's meanings and history.